Propositional Justification and Infinitism - Tito Flores (Manuscrito)
ABSTRACT This essay presents the chief reasons for making a distinction between propositional and doxastic justification and, also, points out two things: (1) no theory of propositional justification implies a theory of doxastic justification; (2) infinitism is, essentially, a theory of propositional justification. Additionally, this paper tries to shed some light on the three conjointly sufficient conditions for a proper infinitist view of propositional justification.